Mechanical Properties of AM Polymer Specimens Under Bending Stress - Vasileios D. Sagias; Dimitrios G. Papageorgiou; Achilleas Pappas; Constantinos I. Stergiou (Applied Mechanics)
Additive Manufacturing, or 3D Printing, is based on manufacturing physical objects by sequential deposition of layers of material. Although the usage of AM is growing, no straightforward methodology exists to produce parts with specific, or optimized, mechanical properties. In this work, an approach for optimizing the mechanical properties of AM specimens under bending stress is presented, using DOE. For the experimental procedure, Fused Deposition Modeling (FDM) technology was used along with Polylactic acid (PLA) as the in-process material. Nozzle temperature, printing speed, infill pattern and printing orientation were selected as manufacturing factors to be optimized to achieve so maximum load and deflection to be acquired. Both optimized sets of values were increased by 53% and 28%, respectively, and were experimentally checked to validate the accuracy of the approach.